Advances in mathematics and applications : celebrating 50 years of the Institute of Mathematics, Statistics and Scientific Computing, University of Campinas /: celebrating 50 years of the Institute of Mathematics, Statistics and Scientific Computing, University of Campinas. (2018) - Unknown
No abstract available